Alkali-activated and geopolymer materials developed using innovative manufacturing techniques: A critical review. (11th October 2021) - Gökçe, H.S.; Tuyan, M.; Nehdi, M.L.
Highlights: Production techniques for AAM and geopolymers materials are critically reviewed. Enhanced understanding of engineering properties is gained. Using special production techniques achieves desired performance & eco-efficiency. Inherent problems could be mitigated using novel production techniques. Research needs to overcome existing hurdles are identified. Abstract: The manufacturing of geopolymers and alkali-activated materials for precast and cast in-situ construction applications could be achieved using suitable production techniques, such as one-part production, pre-setting pressure and hot pressing, two-stage concreting, and 3-dimensional printing. Adequate selection and tailoring of the manufacturing methodology are imperative for overcoming characteristic application problems of these materials and achieving eco-efficiency and superior engineering properties. With distinctive benefits including rapid solidification, lower cost, saving natural resources, less energy consumption, and reduced carbon footprint, alkali-activated and geopolymer composites have emerged as a strong contender for replacing conventional concrete in diverse construction applications. Critical analysis of the literature on innovative production methods indicates that the one-part production technique is promising for the eliminating design complexity of these mixtures. The pre-setting pressure and hot pressing applications would allow the achievement of superior physical and mechanical characteristics in a short period of time, especially for the precast industry. The workability and setting problems of alkali-activated materials could be overcome using the two-stage concreting methodology. To be used in 3D printing of alkali-activated and geopolymer materials, remarkable development is required in terms of rheological aspects. Accordingly, this paper surveys pertinent and recent literature and critically reviews the state-of-the-art of alternative production techniques of alkali-activated and geopolymeric materials, along with its use in recent applications, identifies pertinent knowledge gaps, and defines future research directions.